Les pratiques traditionnelles de l’utilisation des produits forestiers non ligneux(PFNL) d’origine végétale cas : d’écorce, graines, feuilles, fruits et racines de (Myrianthus arboreus) par les populations rurales de Kalima/Pangi/Maniema/RDC - Ir. ADAM ZAKUANI; Célestin, BARUANI BWANAMUDOGO (IJRDO - Journal of Social Science and Humanities Research, 2019)
Our research focused on "traditional practices of using non-wood forest products (NTFPs) of plant origin case: bark, seed, leaves, fruits and roots of Myrianthusarboreus by rural populations of Kalima / Pangi / Maniema The present study aims to determine the traditional phyto-therapeutic values, to identify the diseases, the traditional methods of treatment in order to verify the marketing of these non-wood forest products coming from Myrianthusarboreus in our Middle. The free interview of a pre-established questionnaire on a sample of 80 people grouped from 4 target districts of the rural municipality of Kalima and the documentary method allowed us to collect some information on the traditional practices of non-timber forest products of Myrianthusarboreus. as drugs. Our results show that rural populations have a good grasp of these resources and their methods of treatment and they have knowledge of the use of seeds, leaves, bark and roots to cure certain diseases such as: angina, diarrhea, boils, lumbar pain, diabetes, gonorrhea.